2021
DOI: 10.1002/nau.24618
|View full text |Cite
|
Sign up to set email alerts
|

Patient preference elicitation instrument, OABCare, to facilitate shared decision‐making in the care of overactive bladder

Abstract: Aims: To describe the development and feasibility of a preference elicitation instrument, OABCare, using choice-based adaptive conjoint analysis (ACA) among patients with overactive bladder (OAB). Methods: This was a two-phase study. In Phase 1, an extensive literature review along with patient and provider focus groups yielded the attributes and levels for our OABCare instrument. The hierarchical Bayesian random-effects model generated utilities and mean relative importance scores of treatment attributes. Pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…In addition to patients' desire to reduce OAB symptoms and avoid adverse effects, caregiver burden concerns, social interaction constraints, and psychological distress have all been found to be important attributes to patient decision making. 40,42 Qualitative studies have reinforced this finding, showing that the impact of OAB on social interaction and daily life were also central reasons to pursue third-line therapy for OAB. 43 Patient preferences may also help explain low rates of third-line therapy.…”
Section: Patient Preferences In Oab Treatment Decisionsmentioning
confidence: 97%
See 4 more Smart Citations
“…In addition to patients' desire to reduce OAB symptoms and avoid adverse effects, caregiver burden concerns, social interaction constraints, and psychological distress have all been found to be important attributes to patient decision making. 40,42 Qualitative studies have reinforced this finding, showing that the impact of OAB on social interaction and daily life were also central reasons to pursue third-line therapy for OAB. 43 Patient preferences may also help explain low rates of third-line therapy.…”
Section: Patient Preferences In Oab Treatment Decisionsmentioning
confidence: 97%
“…In 2021, two decision aids have emerged for OAB: OABcare uses DCE to guide preference elicitation for individual patients while a Streamlined is a mobile patient decision aid. 40 Streamlined, was created based on qualitative interviews showing that women with OAB expressed need for personalization of treatment options and desire to participate in decisions. 44 The study found that patients spent less than 8 min with the application, resulting in decreased decisional conflict.…”
Section: Oab Decision Aidsmentioning
confidence: 99%
See 3 more Smart Citations